A representação social nos discursos de custodiados em depoimentos - Boone, Maruza Brasil (2018)
The main objective of this work is to analyze how social actors in custody construct their social representations from linguistic choices polarized discursive structures. We chose as corpus of research 408 responses uttered by custodians through an open questionnaire, therefore, a discursive genre, apprehended as speeches that guided us in the choice of our theoreticalmethodological framework. The analysis of the answers of the questionnaire presents itself as something complex, not only involving information of linguistic nature, but also of social, historical, cultural and cognitive character, since discursive analysis cannot be seen outside the social environment, the actors and the place where these discourses were processed, as well as the ideologies present during the discursive process. Adopted a multidisciplinary and sociocognitive proposal of Critical Discourse Analysis (ACD), by Van Dijk (1999; 2012; 2014; 2015) who is concerned with minorities and with the inequalities in a critical perspective. In addition, this proposal allows us to understand the established relationship between society, discourse and cognition. For the study of the history of prisons and punishments in the social context, we count on the contributions of authors such as Foucault (1987, 2002); Durkheim (2014), Beccaria (2002). To carry out the analyzes, we delimited categories of the sociocognitive proposal of van Dijk, which allowed us to constitute a table with the categories selected for the analysis procedure. The results point out that the lexical choices of the custodians' discourses are based on questions that turn to polarizations and are revealed in effective strategies in the maintenance of ideologies, consequently, of how these social actors represent socially.